Pulse-shaped two-photon excitation of a fluorescent base analogue approaches single-molecule sensitivity. Issue 45 (9th November 2018) - Fisher, Rachel S.; Nobis, David; Füchtbauer, Anders F.; Bood, Mattias; Grøtli, Morten; Wilhelmsson, L. Marcus; Jones, Anita C.; Magennis, Steven W.
Abstract : Ultrasensitive detection of DNA is achieved via two-photon excitation of a fluorescent base analogue. Abstract : Fluorescent nucleobase analogues (FBAs) have many desirable features in comparison to extrinsic fluorescent labels, but they are yet to find application in ultrasensitive detection. Many of the disadvantages of FBAs arise from their short excitation wavelengths (often in the ultraviolet), making two-photon excitation a potentially attractive approach. Pentacyclic adenine (pA) is a recently developed FBA that has an exceptionally high two-photon brightness. We have studied the two-photon-excited fluorescence properties of pA and how they are affected by incorporation in DNA. We find that pA is more photostable under two-photon excitation than via resonant absorption. When incorporated in an oligonucleotide, pA has a high two-photon cross section and emission quantum yield, varying with sequence context, resulting in the highest reported brightness for such a probe. The use of a two-photon microscope with ultrafast excitation and pulse shaping has allowed the detection of pA-containing oligonucleotides in solution with a limit of detection of ∼5 molecules, demonstrating that practical single-molecule detection of FBAs is now within reach.